The effect of task-oriented training on the muscle activation of the upper extremity in chronic stroke patients - Park, JuHyung (Journal of Physical Therapy Science, 2016)
[Purpose] The aim of this study was to determine the effects of task-oriented training on upper extremity muscle activation in daily activities performed by chronic stoke patients. [Subjects and Methods] In this research, task-oriented training was conducted by 2 chronic hemiplegic stroke patients. Task-oriented training was conducted 5 times a week, 30 minutes per day, for 2 weeks. Evaluation was conducted 3 times before and after the intervention. The Change of muscle activation in the upper extremity was measured using a BTS FreeEMG 300. [Results] The subjects’ root mean square values for agonistic muscles for the reaching activity increased after the intervention. All subjects’ co-coordination ratios decreased after the intervention in all movements of reaching activity. [Conclusion] Through this research, task-oriented training was proven to be effective in improving the muscle activation of the upper extremity in chronic hemiplegic stroke patients.